Financial Effect On Stock Price Based Chemistry and Industry Listed in Indonesia Stock Exchange Year 2014-2016 - Kartika Hendra, Yuliyantina Safitri, Siti Nurlaela & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This study aimed to determine the effect of the financial performance of the stockprice on the company and basic chemical industry listed in Indonesia StockExchange either partially or simultaneously. Samples taken as many as 11companies in the period 2014-2016. The type of data in this study using secondarydata from the financial statements. The independent variable in this study is theDAR, ROA, CR, and EPS. As for the dependent variable in this study is the stockprice. The data collection technique using purposive sampling method. The data inthis study using multiple regression analysis. The first results of this study from thecalculation of DAR, ROA, and CR simultaneously no significant effect on stockprices. While the EPS of the most dominant variable influence on the companysstock price base and chemical industry.Keywords: [DAR, ROA, CR, EPS, Price Stocks]